ENDEMISM AS A PALAEOBIOGEOGRAPHIC PARAMETER OF BASIN HISTORY ILLUSTRATED BY EARLY- AND MID-LIASSIC PERI-TETHYAN AMMONITE FAUNAS - Dommergues J.L.; El Hariri K. (My University, 2002)
Episodes of endemism during Sinemurian-Pliensbachian times are described from synthetic data (publications and unpublished collections) about ammonite faunas of the western reaches of the Tethys. The Lusitanian, Sub-Betic and High Atlas basins receive special attention. The study shows that (1) endemism occurs principally in the Lusitanian and High Atlas basins, which are the most confined palaeogeographic structures; (2) it tends to occur synchronously in different basins but involving different taxa, i.e. it is independent of phylogeny; (3) it is not obviously correlated with relative sea-level at any given time. However, the fact that episodes of endemism coincide with second-order regressive phases suggests some connection between sea-level falls, independently of the sea level, and the development of endemic faunas.
Keywords: LOWER JURASSIC; TETHYS; ENDEMISM; EVOLUTION; AMMONITES; Pliensbachian; Sinemurian; Mesozoic::Jurassic::Lower::Pliensbachian; Мезозой::Юрская::Нижний::Плинсбахский; Мезозой::Юрская::Нижний::Синемюрский; Mesozoic::Jurassic::Lower::Sinemurian